Posted by **olivia** on Sunday, March 25, 2012 at 8:10pm.

1/tanx-secx+ 1/tanx+secx=-2tanx

so this is what I did:

=tanx+secx+tanx-secx

=(sinx/cosx)+ (1/cosx)+(sinx/cosx)-(1/cosx)

=sinx/cosx+ sinx /cosx= -2tanxI

but I know this can't be correct because what I did doesn't end as a negatvie:( please help

## Answer This Question

## Related Questions

- Pre-Calc - Trigonometric Identities Prove: (tanx + secx -1)/(tanx - secx + 1)= ...
- Trigonometry Check - Simplify #3: [cosx-sin(90-x)sinx]/[cosx-cos(180-x)tanx] = [...
- Math - Im really struggling with these proving identities problems can somebody ...
- Pre-Calculus - How do you verify: 1.) sinxcosx+sinx^3secx=tanx 2.) (secx+tanx)/(...
- Precalculus/Trig - I can't seem to prove these trig identities and would really ...
- Simplifying with Trigonometry Identities - Hi, I am a senior in High School ...
- math - 1. (sinx/cscx)+(cosx/secx)=1 2. (1/sinxcosx)-(cosx/sinx)=tanx 3. (1/1+cos...
- Math - I'm only aloud to manipulate one side of the problem and the end result ...
- maths - trigonometry - I've asked about this same question before, and someone ...
- Calculus - Q: If y=sinx/(1+tanx), find value of x not greater than pi, ...

More Related Questions